Building moonshots : 50+ ways to turn radical ideas into reality - Carleton, Tamara; Cockayne, William R. (John Wiley & Sons, Inc., 2023)
"Building Moonshots is the seminal, go-to source for visionaries, game changers, and leaders seeking to imagine and achieve the almost impossible. If you are looking to scale your vision bigger and bolder, pursue groundbreaking goals, or transform into a visionary organization, you need Building Moonshots. The book identifies and describes 50+ ways for building radical innovative solutions and addressing the world's grand challenges in order to create a better future. Each way of thinking or way of doing in the book provides a proven practice for converting big dreams into reality. All the ways are further organized by categories to help you at any point in the process -- how to start, where to wander, when to bet big, how to invest, what to communicate, when to play the long game, and more"--